2023
DOI: 10.3389/fneur.2023.1174425
|View full text |Cite
|
Sign up to set email alerts
|

Variants in genes related to inflammation and endothelial function can increase the risk for carotid atherosclerosis in southwestern China

Abstract: AimTo investigate the potential association between polymorphisms in genes involved in endothelial function, inflammation and carotid atherosclerosis.MethodsThis was a three-center, population-based sectional survey conducted in Sichuan province of southwestern China. We randomly selected 8 different communities in Sichuan, and the residents in each community volunteered to participate in the survey by face-to-face questionnaire. A total of 2,377 residents with high stroke risk population in the 8 communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…For instance, Gardener et al (13) evaluated the associations between carotid plaque and 197 variants in 43 genes implicated in inflammation and endothelial function and demonstrated that the variants in 10 genes (IL6R, TNF, NOS2A, IL1A, TNFSF4, ITGA2, PPARA, TLR4, HABP2, and VCAM1) were associated with carotid plaque in the Northern Manhattan population. Similarly, our previous studies have also shown that specific single nucleotide polymorphisms (SNPs) in genes related to inflammation and endothelial function and high-risk interaction among HABP2 rs7923349, ITGA2 rs1991013, IL1A rs1609682, and NOS2A rs8081248, the interaction between ITGA2 rs4865756 and HABP2 rs7923349, and interaction among ITGA2 rs1991013, IL1A rs1609682, and HABP2 rs7923349 were associated with carotid plaque vulnerability (10), carotid stenosis and IMT (14,15), and increased risk of carotid atherosclerosis (16), respectively. However, Gardener et al and our previous studies did not prospectively investigate the association of these variants and carotid atherosclerosis with subsequent stroke and other vascular events.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…For instance, Gardener et al (13) evaluated the associations between carotid plaque and 197 variants in 43 genes implicated in inflammation and endothelial function and demonstrated that the variants in 10 genes (IL6R, TNF, NOS2A, IL1A, TNFSF4, ITGA2, PPARA, TLR4, HABP2, and VCAM1) were associated with carotid plaque in the Northern Manhattan population. Similarly, our previous studies have also shown that specific single nucleotide polymorphisms (SNPs) in genes related to inflammation and endothelial function and high-risk interaction among HABP2 rs7923349, ITGA2 rs1991013, IL1A rs1609682, and NOS2A rs8081248, the interaction between ITGA2 rs4865756 and HABP2 rs7923349, and interaction among ITGA2 rs1991013, IL1A rs1609682, and HABP2 rs7923349 were associated with carotid plaque vulnerability (10), carotid stenosis and IMT (14,15), and increased risk of carotid atherosclerosis (16), respectively. However, Gardener et al and our previous studies did not prospectively investigate the association of these variants and carotid atherosclerosis with subsequent stroke and other vascular events.…”
Section: Introductionmentioning
confidence: 68%
“…Based on our previous community-based cross-sectional survey (16), we undertook this multicenter prospective cohort study in Sichuan, southwestern China, from May 2015 to January 2020. This study is a part of the CNSSS, and the study protocol was approved by the Ethics Committee of the Affiliated Hospital of Southwest Medical University, Suining Central Hospital, and the People's Hospital of Deyang City.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations